Quantized conductance coincides with state instability and excess noise in tantalum oxide memristors - Wei Yi (Nature Portfolio, 2016)
Oxide memristors exhibit noise in excess of 2–4 orders of magnitude above the baseline at quantized conductance states. Here, the authors measure anomalous electrical noise at these states in tantalum oxide memristors and relate it to thermally-activated atomic fluctuations by numerical simulations.